Effects of Feeding Rate and Larval Density on Development in Aedes albopictus (Diptera: Culicidae) (Bangladesh Journal of Zoology, 2025)
Larval density and food availability can act as limiting factors in the container habitat of Aedes albopictus mosquito vector species. Under laboratory conditions, two experiments were conducted to investigate the effects of feeding rates and larval density on the immature development of Ae. albopictus larvae. A cohort of 30 larvae were reared in 300 ml tap water with low and high amounts of food supplied for feeding rates experiment. For density experiment, 20 larvae in low density and 60 larvae in high density treatment was reared with same amount of food in 200 ml tap water. Each treatment was replicated five times. Larvae were reared from hatching to adult emergence with food provisioned per capita and per instar basis. A one-way ANOVA revealed significant effects of the experimental treatments on survivorship, age at pupation and development time. Maximum survivorship of 93.33 ± 4.08% was observed from high food treatment and a reduced survival rate of 75.67 ± 6.08% was found from high density treatment. A prolonged development time of 25.34 ± 0.73 days was resulted from low food treatment and a short development period of 10.29 ± 0.50 days from high food treatment. Male-biased sex ratios (male: female) were recorded from low food (81: 41) and high-density (150:77) treatments respectively. This study supports that survivorship and larval development are influenced by larval density and availability of nutrition levels in container breeding habitats, with potential implications for developing vector control strategies.Bangladesh J. Zool. 53(2): 219-229, 2025